The Climate Change Impact of Material Use - Arno Behrens (Intereconomics, 2016)
There is a direct physical relationship between the quantity of raw materials used in industrial processes, the energy required and, hence, GHG emissions. The latter are emitted in all stages of the product lifecycle: extraction, production, consumption and waste management.
Keywords: 330; Ressourcennutzung; Klimawandel; Wirkungsanalyse